Cigarette Smoke Extract Produces Superoxide in Aqueous Media by Reacting with Bicarbonate - Jung-Min Park (MDPI AG, 2021)
The toxicity of cigarette smoke (CS) is largely attributed to its ability to generate reactive oxygen species (ROS). Reportedly, CS generates superoxide in cell culture systems by stimulating the cells to produce superoxide and through direct chemical reactions with components of the culture media. In this study, we investigated CS-induced superoxide formation in biocompatible aqueous media and its characteristics. Cigarette smoke extract (CSE) and total particulate matter (TPM) were prepared from the mainstream smoke of 3R4F reference cigarettes. CSE and TPM generated superoxide in Hank’s balanced salt solution (HBSS), Dulbecco’s modified Eagle media (DMEM), and blood plasma, but not in distilled water and phosphate-buffered saline. Each constituent of HBSS in solution was tested, and bicarbonate was found to be responsible for the superoxide generation. More than half of the superoxide formation was abolished by pretreating CSE or TPM with peroxidase, indicating that the substrates of peroxidase, presumably peroxides and peroxy acids, mainly contributed to the superoxide production. In conclusion, the presence of bicarbonate in experimental conditions should be considered carefully in studies of the biological activity of CS. Furthermore, the local amount of bicarbonate in exposed tissues may be a determinant of tissue sensitivity to oxidative damage by CS.